PENGARUH SISTEM PRODUKSI DAN STRATEGI BAURAN PEMASARAN TERHADAP KEBERHASILAN USAHA INDUSTRI OLAHAN MAKANAN BERBAHAN BAKU PISANG (Musa paradisiaca) - Iman, Manirul; Dasipah, Deuis; Gantini, Tuti (Journal of Innovation and Research in Agriculture, 2024)
This study aims to analyze the business performance of the processed food industry made from banana raw materials and the influence of production systems and marketing mix strategies on business success. The respondent determination technique used was stratified random proportionally based on the type of business, 65 respondents were selected. The analysis technique used is path analysis. The results of the study showed that there are 10 types of processed food industry made from bananas which are characterized: banana raw materials obtained locally at price of Rp. 2,500/kg to Rp. 5,000/kg, using simple technology, employing 2-3 workers, added value around Rp. equal to IDR 262,500/kg of raw material. . Performance of the Production System which includes the dimensions of: product planning; input/raw material subsystem; the process subsystem and the control subsystem in the banana-based processed food industry obtained an achievement of 80.86% with good criteria. Marketing Mix Strategy (Mix Marleting Strategic) which includes dimensions: product; prices; place; promotion in the processed food industry based on banana raw materials obtained an achievement of 75.29% good criterion. The success of the processed food industry based on banana raw materials which includes dimensions: quality of banana products; productivity; continuity, and the benefits obtained by the achievement of 77.71% criteria are good. There is a positive correlation between the Marketing Mix Strategy and the Production System as indicated by the correlation coefficient number r = 0.854 meaning that the better the Marketing Mix strategy is implemented, the better the Production System will be and vice versa. The production system and marketing mix strategy have a significant positive effect on business success in the processed food industry based on banana raw materials. The production system contribution was 51.04% greater than the contribution of the Marketing Mix Strategy of 32.78%. The remaining 16.18% is influenced by other factors.